Improving the breeding capabilities of short-term estrus synchronized Ossimi sheep using pregnant mare serum gonadotropin loaded chitosan-nanoparticles - Shehabeldin, Ahmed M.; Salama, Maha S.; Omar, Mohamed E. A.; AbdEl-Rafaa, Liza A.; Ashour, Mohey A.; Hassan, Mahmoud A. E.; El-Shereif, Abdelghany A.; Abdelmegeid, Mohamed; Shukry, Mustafa; Elolimy, Ahmed A. (Frontiers in Veterinary Science, 2025)
IntroductionThe present study evaluated the efficacy of pregnant mare serum gonadotropin (PMSG) and PMSG encapsulated in chitosan-tripolyphosphate nanoparticles in enhancing reproductive performance in short-term progesterone estrus-synchronized Ossimi ewes.MethodsSeventy-five healthy ewes were randomly assigned to three groups (n = 25 per group). Group 1 (representing current standard practice) received 25 mg progesterone acetate for 7 days, 600 IU PMSG on day 6, and 250 μg prostaglandin F2α (PGF2α) on day 7. Group 2 followed the same regimen as Group 1, except for administering 300 IU of PMSG-loaded chitosan-tripolyphosphate nanoparticles on day 6, followed by an intramuscular injection of 250 μg PGF2α on day 7. Group 3 received 150 IU of PMSG-loaded chitosan-tripolyphosphate nanoparticles on day 6 and 250 μg PGF2α on day 7. Estrus detection occurred between days 7 and 11, with a gonadotropin-releasing hormone (GnRH) injection at breeding.Results and discussionGroup 1 had a significantly shorter onset of estrus (54.40 ± 4.50 h; p < 0.05) compared to Group 2 (71.60 ± 0.51 h) and Group 3 (72.20 ± 4.81 h). Pregnancy and lambing rates were highest in Group 2 (100%; p < 0.05), and Group 2 produced more fetuses (40) than Group 1 (30) and Group 3 (25). Fecundity was also highest in Group 2 (160%; p < 0.05). Follicular diameter was greater in Group 2 on day 9, although the number of large follicles was similar across groups. The number of corpora lutea significantly increased on day 7 compared to day 0 in all groups. Progesterone levels peaked on day 7 and declined by day 9 across all groups. These results suggest that administering 300 IU of PMSG encapsulated in chitosan-tripolyphosphate nanoparticles can enhance reproductive performance more effectively than conventional PMSG, offering a promising strategy to improve fertility in short-term progesterone-synchronized ewes.